Surgical vascular access in the porcine model for long-term repeatedblood sampling - Lombardo, C.; Damiano, G.; Cassata et al., G. (Acta Biomedica Atenei Parmensis, 2010)
A simple technique for implanting a long-term jugular catheter in piglets under general anesthesia is described. We report our experience in 10 young female pigs with a body weight of 20-30 Kg. The surgical procedure involves implantation of a jugular central venous catheter (11Fr polyurethane) tunneled in the subcutaneous fat layer of the neck. This procedure may be performed in about 15 minutes. The maintenance of the catheter is described which allows several daily blood samples to be taken. This procedure reduces both the stress in piglets and the chance of catheter dislodgement due to the animals scratching or rubbing. Blood sampling can be easily performed with a low incidence of infection or thrombosis.